2004
DOI: 10.1111/j.0022-4537.2004.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Existence and Coexistence in Acre: The Power of Educational Activism

Abstract: This article presents a five-year action-research project of systemic change toward coexistence in Acre, a mixed Arab-Jewish city in Israel. Educational activism was the basis for this project. Because education in Acre was closely interwoven with discriminative politics, this project used a citywide systemic approach consisting of three layers: (a) work in schools that used cooperative learning to increase achievement, (b) work with parents in school-family literacy partnerships, and (c) work with the city's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A multisystemic approach to reducing prejudice was suggested by several scholars (Coleman & Deutsch, 2000; Pruitt & Olczak, 1995) who advocated addressing simultaneously issues related to multiple modalities including motivation, affect, cognition, behavior, and social environment. Examples of such programs were provided by Desivilya (2004) and Hertz-Lazarowitz (2004). The CEP strives to integrate the aforementioned approaches, including McKown’s (2005) ecological theory that suggested advancing the practice of school-based prejudice reduction intervention by utilizing a combination of interventions that originate from varied theoretical traditions.…”
Section: Prejudice Reduction Programs: Theory and Researchmentioning
confidence: 99%
“…A multisystemic approach to reducing prejudice was suggested by several scholars (Coleman & Deutsch, 2000; Pruitt & Olczak, 1995) who advocated addressing simultaneously issues related to multiple modalities including motivation, affect, cognition, behavior, and social environment. Examples of such programs were provided by Desivilya (2004) and Hertz-Lazarowitz (2004). The CEP strives to integrate the aforementioned approaches, including McKown’s (2005) ecological theory that suggested advancing the practice of school-based prejudice reduction intervention by utilizing a combination of interventions that originate from varied theoretical traditions.…”
Section: Prejudice Reduction Programs: Theory and Researchmentioning
confidence: 99%
“…Lustig (2003) found that the study of a remote interethnic conflict (in this case, the Irish) helped Israeli youngsters become more willing to acknowledge the two-sided nature of the narratives involved in the local conflict. Hertz-Lazarowitz (2004) presented successful results emanating from a 5-year action-research project of systemic change toward coexistence in the mixed Arab-Jewish city of Acre. The project was successful until the second Intifada erupted.…”
Section: The Effectiveness Of Peace Education Programsmentioning
confidence: 99%
“…There are some 'private' educational programmes available for schools that deal with Palestinian-Israeli relationships. These programmes are not part of the general curriculum, but schools can, on the principals' initiative, participate in them (Abu-Nimer, 2004;Hertz-Lazarowitz, 2004). Obviously there are advantages to such programmes and meetings, but they are affected by three main problems: (1) in most of them, the dominant (virtually the only) language of communication is Hebrew; (2) although some programmes deal with the conflict and others try to find shared interests, most of them are based on culture (folklore); and (3) most of the programmes are either one-time events, or have long intervals between them.…”
Section: Challenging the Reality: Jewish-arab Meetingsmentioning
confidence: 99%